2017
DOI: 10.5696/2156-9614-7.15.71
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals and Polycyclic Aromatic Hydrocarbons in Soil from E-waste Dumpsites in Lagos and Ibadan, Nigeria

Abstract: Background.Soil contamination from heavy metals and polycyclic aromatic hydrocarbons (PAHs) released during informal e-waste processing and disposal poses human and ecological health risks in Nigeria.Objectives.This study assesses the levels of heavy metals and PAHs in soils of e-waste dumpsites in Lagos and Ibadan, Nigeria.Methods.Composite soil samples were collected at depths of 0–15 cm, 15–30 cm and 30–45 cm from major e-waste dumpsites in Lagos and Ibadan and analyzed for lead (Pb), cadmium (Cd), copper (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Hence, PAHs have been described as the anthropogenic micro-pollutant with most environmental influence [11]. In the same manner, incineration of waste tends to release semi-volatile hydrocarbon compounds, such as PAHs into the atmosphere [7,12,13], thereby increasing the exposure routes for PAHs in the environment. Overall, the poor waste management practise of dumping un-segregated wastes along river banks tends to release inorganic and organic micro-pollutants directly into the water body, thereby enhancing the movement of such contaminants along coastal waters, before emptying them into the open sea waters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, PAHs have been described as the anthropogenic micro-pollutant with most environmental influence [11]. In the same manner, incineration of waste tends to release semi-volatile hydrocarbon compounds, such as PAHs into the atmosphere [7,12,13], thereby increasing the exposure routes for PAHs in the environment. Overall, the poor waste management practise of dumping un-segregated wastes along river banks tends to release inorganic and organic micro-pollutants directly into the water body, thereby enhancing the movement of such contaminants along coastal waters, before emptying them into the open sea waters.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring sources of pyrogenic PAHs release nominal levels in the environment, which emanates mainly from volcanic lava eruptions and incomplete burning of woodland fires, etc [22]. Other sources of PAHs include coal tar and crude oil [21] and electronic wastes [13], amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the metal levels to those reported in previous studies in the same areas, it is found that metal concentrations are increasing (Olafisoye et al, 2013;Isimekhai et al, 2017;Adesokan and Gilbert, 2016;Adeyi, 2017). The metal concentration at the burning sites were also higher than the concentration reported in studies in China (Yekeen et al, 2016;Awasthi et al, 2016a).…”
Section: Implications Of High Metals Concentrations In the Environmentmentioning
confidence: 44%
“…The strengths of this study are its focus on different e-waste sites in each city, analyses of more number of metals that are not usually reported in other studies, the comparison of metal concentrations in various environmental samples (top soils, floor dusts, roadside dust, and direct dust from electronics) from different e-waste recycling sites and corresponding control sites, and the comparison of the extent of metal pollution at ewaste sites across the three cities in two different geopolitical zones in Nigeria. So far most studies (Isimekhai et al, 2017;Adesokan and Gilbert, 2016;Adeyi, 2017;Adaramodu et al, 2012) on metal pollution due to informal e-waste recycling sites focused on one location and usually on one type of environmental sample only. Therefore, these did not provide a comprehensive view on the extent to which heavy metal pollution from these activities is a problem.…”
Section: Discussionmentioning
confidence: 99%
“…In the soil, these organic compounds have low mobility, high durability, and high affinity to soil organic matter [6]. It has been reported as well that, at dumpsites where solid wastes are burned, contamination by heavy metals is often accompanied by contamination by organic compounds [7,8].…”
Section: Introductionmentioning
confidence: 99%